2022
DOI: 10.1128/spectrum.02279-21
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Bacterial Airways Infection in Stable Severe Asthma Using Oxford Nanopore Sequencing Technologies

Abstract: The human airways were once thought sterile in health. Now metagenomic techniques suggest bacteria may be present, but their role in asthma is not understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Although NTHi is often considered rather innocuous, our data support the growing body of data that this pathogen has a relatively unique ability to persist within the airways and drive ongoing and recurrent neutrophilic inflammation in type-2 low asthma, and therefore is likely to merit more attention by clinicians. This is a common clinical scenario and indeed using Nanopore long-read sequencing we have recently identified NTHi in the lower airways in 35% of a pilot cohort of patients with severe asthma ( Jabeen et al., 2022 ). Further larger cohorts are required to define the prevalence of this and other specific potentially pathogenic bacteria in well-defined cohorts with airways disease.…”
Section: Discussionmentioning
confidence: 94%
“…Although NTHi is often considered rather innocuous, our data support the growing body of data that this pathogen has a relatively unique ability to persist within the airways and drive ongoing and recurrent neutrophilic inflammation in type-2 low asthma, and therefore is likely to merit more attention by clinicians. This is a common clinical scenario and indeed using Nanopore long-read sequencing we have recently identified NTHi in the lower airways in 35% of a pilot cohort of patients with severe asthma ( Jabeen et al., 2022 ). Further larger cohorts are required to define the prevalence of this and other specific potentially pathogenic bacteria in well-defined cohorts with airways disease.…”
Section: Discussionmentioning
confidence: 94%
“…In pediatric asthma, small studies have reported increased frequency of IL-17 + MAIT cells in bronchoalveolar lavage (142) and blood (143) of patients presenting with severe exacerbations, however no comparisons were made with health when sampling the lower airway (142). In adult disease Haemophilus influenzae has emerged as the commonest potentially pathogenic organism in the airway, associated with sputum neutrophilia and altered microbial diversity, namely reduction in Streptococcus, Gemella and Porphyromonas taxa (135,136,144,145). In a large bronchoscopy study no evidence of increased IL-17A in serum, sputum or BAL was found in asthma nor was there an increase in IL-17 + T cell populations (Th17 or gdT cells).…”
Section: The Lower Airwaymentioning
confidence: 99%
“…Moreover, it is unclear how common this trait is, or to what extent heterogeneity of the microbiome matters to predicting treatment response. In a pilot study of metagenomic analysis using quantitative PCR and Oxford nanopore sequencing, we identified H. influenzae as the dominant airway pathogen in eight out of 23 people with severe asthma [ 158 ]. The presence of Haemophilus at high abundance was significantly and invariably associated with sputum neutrophilia, as was the presence of M. catarrhalis , in two out of 23 samples.…”
Section: Clinical Application: Efficacy Of Macrolides In Asthmamentioning
confidence: 99%